The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4103/ijo.ijo_565_20
|View full text |Cite
|
Sign up to set email alerts
|

Isolated intraocular histiocytosis—A rarely reported entity masquerading clinically as uveitis

Abstract: An immunocompetent, 25-year-old gentleman with bilateral chronic uveitis presented to various uveitis clinics at different points of time with documented typical clinical features of Toxoplasma Chorioretinitis (Headlight in fog appearance), Behcet's Disease (Hypopyon with peripheral retinal vasculitis), and Presumed Ocular Tuberculosis (Granulomatous Intermediate Uveitis with positive Interferon-gamma release assay) and had been treated with anti-toxoplasma drugs, oral prednisolone, and immunomodulation with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In one case, a diagnosis of choroidal melanoma was made, but immunohistochemical studies revealed LCH [10], and in the second eye, the iris portion of an iridociliochoroidal mass was found to be LCH after fine-needle aspiration [7]. Some reported vitreous biopsy for diagnosis of intraocular LCH [15], whereas others made the diagnosis based on a systemic history of LCH [11,16,17], as we did for our patient.…”
Section: Discussionmentioning
confidence: 59%
“…In one case, a diagnosis of choroidal melanoma was made, but immunohistochemical studies revealed LCH [10], and in the second eye, the iris portion of an iridociliochoroidal mass was found to be LCH after fine-needle aspiration [7]. Some reported vitreous biopsy for diagnosis of intraocular LCH [15], whereas others made the diagnosis based on a systemic history of LCH [11,16,17], as we did for our patient.…”
Section: Discussionmentioning
confidence: 59%